Orchid And Anthurium Industry In Kerala -A Stuidy Of Homescale Unitsn - Prakash Kumar Karan (Department of Agricultural Economics, College of Horticulture, 1999)
Orchid and anthurium are identified as the most important flowers with commercial potential suitable for the state. Present study was aimed to investigate the economics of commercial production and marketing of orchid and anthurium in Kerala and to identify the constraints and analyze future prospects of these two crops in the State. The study was conducted with a sample of 80 growers for each crop. Percentage analysis and capital productivity analysis were used to analyze the data. Orchid and anthurium growing units have been studied across three scales of operation, viz., small (upto 500 plants: G-I), medium (500 to 1000 plants: G-II) and large (above 1000 plants: G-I1I) for a standard of 100 plants in each categories. 1. Orchid Total cost of cultivation for five years was estimated to be Rs. 17,471 of which about 57.28 per cent was the establishment cost. Per unit cost of cultivation is found increasing towards smaller scale of operation. The total return realized over crop life is found to be about Rs. 36,088. Higher returns were realized from larger scale of operation - varying from Rs. 33,240 to Rs. 40,060. The estimated project worth parameters were well above acceptance level in all the groups. On an average, pay back period was estimated as three years, net present value as Rs. 9,345, benefit cost ratio as 1.61 and the internal rate of return as 39 per cent. 2. Anthurium. Per unit cost of cultivation of anthurium was little higher than that of orchid and showed similar cost structure and increasing pattern towards smaller groups. Total cost of cultivation for five years was estimated to be Rs. 19,153, about 57.28 per cent of which was the establishment cost. The total return realized over crop life was found to be Rs. 46,236. It varied from Rs. 43,474 to Rs. 53,037 in different scales of operation.